Technology competition and optimal investment timing: A real options perspective - KAUFFMAN, Robert J. (Institutional Knowledge at Singapore Management University, 2005)
Companies often choose to defer irreversible investments to maintain valuable managerial flexibility in an uncertain world. For some technology-intensive projects, technology uncertainty plays a dominant role in affecting investment timing. This article analyzes the investment timing strategy for a firm that is deciding about whether to adopt one or the other of two incompatible and competing technologies.We develop a continuous-time stochastic model that aids in the determination of optimal timing for managerial adoption within the framework of real options theory. The model captures the elements of the decision-making process in such a way so as to provide managerial guidance in light of expectations associated with future technology competition. The results of this paper suggest that a technology adopter should defer its investment until one technology’s probability to win out in the marketplace and achieve critical mass reaches a critical threshold. The optimal timing strategy for adoption that we propose can also be used in markets that are subject to positive network feedback. Although network effects usually tend to make the market equilibrium less stable and shorten the process of technology competition, we show why technology adopters may require more technology uncertainties to be resolved before widespread adoption can occur.